Reviewing Factors Affecting the Implementation of FAS-EWPA in Small and Medium Enterprises in Denpasar City - Ni Luh Nyoman Sherina Devi; Ida Ayu Ratih Manuari; Yura Karlinda Wiasa Putri (Journal of International Conference Proceedings, 2022)
Small and Medium Enterprises (SMEs) play a role and contribute to the economy in Indonesia. To obtain additional capital from bank and non-bank financial institutions, SMEs are required to include financial statements as a condition for applying for loans. Financial Accounting Standards for Entities without Public Accountability (FAS-EWPA, in Bahasa Indonesia known as SAK-ETAP) is a standard that is intended for business entities that do not have public accountability such as SME entities. This study aims to analyze the effect of providing information and socialization, entrepreneur education, length of business, business size, and perceptions of SME entrepreneurs on the implementation of FAS-EWPA. The research population is SME entrepreneurs who are located and registered with the Denpasar City Cooperatives and Micro, Small, and Medium Enterprises Service. The results showed that the provision of information and socialization, the perception of SME entrepreneurs had a positive effect on the implementation of FAS-EWPA. Meanwhile, entrepreneur education, length of business, and business size have no effect on the implementation of FAS-EWPA. It can be suggested that the role of related parties such as the government needs to be increased in providing socialization about the understanding of FAS-EWPA.Â Keywords: FAS-EWPA, Financial Reporting, SMEs.